Analysis of the Effect of Non-Performing Loan, Return on Assets, Return on Equity and Size on Banking Liquidity Risk (Case Study on Conventional Banks Registered in IDX period 2016 – 2020) - Widyarti, Endang Tri; Widyakto, Adhi; Suhardjo, Yohanes (JDM (Jurnal Dinamika Manajemen), 2022)
In the economy of a country, banking has a big part to do. Banking plays an important role in lending in public and private areas. The function of banking as an intermediary, which the bank is useful as an intermediary between the parties who are sufficient to those in need. This research is focused on areas that have an effect on liquidity risk in banks. The purpose of this research is nothing but to analyze the securities of NPL, ROA, ROE and Size to liquidity risk in banks listing in IDX for the period 2016-2020. The samples used in the research of all banks, both state-owned (SOE) and National Private Banks in Indonesia are recognized in BI from 2016 to 2020. From the criteria obtained by 40 banks, the method used is purposive sampling. The method of analysis used in this research is linear regression, which is tested through classical assumptions with normality, multicollinearity, autocorrelation and heteroscedasticity. The results showed that roa and ROE variables have a good and significant effect on liquidity risk. Medium variable NPL and Size have an adverse and insignificant effect on liquidity risk.